ANALISIS KEMAMPUAN LITERASI KEUANGAN PADA PELAKU USAHA MIKRO, KECIL DAN MENENGAH DI KOTA ENDE - Gabriel Tanusi; Suhartin Mohamad Syarif (JURNAL LENTERA BISNIS, 2025)
This study aims to determine the financial literacy of MSME actors in Ende City in terms of the ability to manage finances, the ability to access financing at financial institutions and the ability to make financial decisions. This type of research is descriptive research. The population of this study were MSME actors in Ende City with a sample size of 92 MSME actors. Data collection techniques using surveys, questionnaires and interviews. The data analysis technique uses descriptive statistical analysis, namely frequency and mean. The results showed that the financial literacy skills of MSME actors in terms of the ability to manage finances were classified as Moderate, the ability to access financing at bank and non-bank financial institutions was classified as Moderate, and the ability to make financial decisions was classified as Moderate.